2015
DOI: 10.1093/chemse/bju075
|View full text |Cite
|
Sign up to set email alerts
|

Taste Responsiveness to Sweeteners Is Resistant to Elevations in Plasma Leptin

Abstract: There is uncertainty about the relationship between plasma leptin and sweet taste in mice. Whereas 2 studies have reported that elevations in plasma leptin diminish responsiveness to sweeteners, another found that they enhanced responsiveness to sucrose. We evaluated the impact of plasma leptin on sweet taste in C57BL/6J (B6) and leptin-deficient ob/ob mice. Although mice expressed the long-form leptin receptor (LepRb) selectively in Type 2 taste cells, leptin failed to activate a critical leptin-signaling pro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
1
1

Year Published

2016
2016
2020
2020

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(12 citation statements)
references
References 44 publications
0
10
1
1
Order By: Relevance
“…This issue warrants further research. It is also important to note that leptin may affect taste-receptor function (Glendinning et al, 2015; Kawai et al, 2000; Meredith et al, 2015; Yoshida et al, 2015), and a contribution of this to our data cannot be excluded.…”
Section: Discussionmentioning
confidence: 89%
“…This issue warrants further research. It is also important to note that leptin may affect taste-receptor function (Glendinning et al, 2015; Kawai et al, 2000; Meredith et al, 2015; Yoshida et al, 2015), and a contribution of this to our data cannot be excluded.…”
Section: Discussionmentioning
confidence: 89%
“…Mechanisms are thought to involve release of endogenous opioids. Interestingly and perhaps indicative of the important role sweet taste plays in food selection and utilization are findings that leptin and endocabbinoids modulate sweet taste function at the receptor level [1516, but see 17]. This modulatory effect of endocabbinoids may thereby play a significant role in regulating energy balance through their ability to alter taste perception.…”
Section: Sweet Taste and Powermentioning
confidence: 99%
“…At oral cavity level, a physiological role of salivary leptin as a growth factor for keratinocyte proliferation was reported [ 21 ]. Recently, Glendinning and colleagues [ 16 ] suggested that salivary leptin might act at leptin receptor level present in taste cells, in a way similar to what was reported for the satiation peptide PYY [ 22 ]. Moreover, Fábián and colleagues [ 23 ], by reviewing the mechanisms of taste perception, hypothesized that leptin, besides having an endocrine action, may act in an exocrine manner, at the level of taste receptor cells.…”
Section: Introductionmentioning
confidence: 79%
“…The influence of leptin at the level of sweet taste perception has been considered in the last years, despite some conflicting results [ 7 , 15 ]. In a recent study [ 16 ] increases in plasma leptin levels did not induce changes in sweet taste responses. Although these authors confirmed the expression of leptin receptors in taste cells, they hypothesized that these receptors in taste cells might be not sufficiently accessible to circulating leptin and that the leptin effect in sweet taste might be through a paracrine route, possibly involving leptin present in saliva.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation